Qualities and translations - Tancredi, Christopher; Sharvit, Yael (Linguistics and philosophy, 2020)
We argue for a new mode of interpretation for attributed attitudes, what we call de translato interpretation. De translato interpretation assigns a meaning to an expression based on the interpretation given to that expression by the attitude subject rather than that standardly given by the attributor (usually the speaker). We argue that this new mode of interpretation is distinct from but compatible with de dicto , de re and de qualitate interpretation. Formally, de translato interpretation is analyzed as introducing a modification in the language used for interpretation, where the modification alters the attributor’s language in such a way as to more closely approximate the presumed language of a perspective holder. Attitude predicates are taken to introduce the perspective of their subject as a parameter of interpretation for the clause they embed.